A negative‐doughnut distal resection margin less than 5 mm does not affect prognosis in rectal cancer. Issue 3 (27th September 2018) - Keranmu, Adili; Liu, Hai‐Ning; Wu, Yu‐Chen; Liu, Tao‐Tao; Li, Cong; Guo, Tian‐An; Liu, Fang‐Qi; Zheng, Hong‐Tu; Xu, Ye
Abstract : Aim: Many issues relating to the distal margin of anterior resection of the rectum still exist. We aimed to investigate whether negative distal resection margin (DRM) and positive DRM in the main specimen with negative doughnut has equivalent prognosis in patients with rectal cancer. Methods: We included 287 patients with rectal cancer, including 69 cases with positive margins and 218 cases with negative margins, all of whom underwent regular follow‐up. Survival rate was calculated using Kaplan‐Meier survival analysis, while the log‐rank test was used to determine statistical difference. Prognostic factors were found using the Cox regression model. Results: There was no significant difference in clinicopathological features between the two groups with the exception of tumor location. Positive findings in the DRM with negative findings in the doughnut resection do not affect the overall survival, local recurrence, or distant metastasis. Factors relating to resection margin, such as the length of resection, negative, or positive findings, were not found to be prognostic. Conclusion: Given postoperative pathology results with positive DRM but negative findings in the doughnut resection, a second surgery was not necessary. Instead, adjuvant radiochemotherapy and close follow‐up will suffice.